Retinal vessel delineation using a brain-inspired wavelet transform and random forest. (September 2017) - Zhang, Jiong; Chen, Yuan; Bekkers, Erik; Wang, Meili; Dashtbozorg, Behdad; Romeny, Bart M. ter Haar
Abstract: This paper presents a supervised retinal vessel segmentation by incorporating vessel filtering and wavelet transform features from orientation scores (OSs), and green intensity. Through an anisotropic wavelet-type transform, a 2D image is lifted to a 3D orientation score in the Lie-group domain of positions and orientations R 2 ⋊ S 1 . Elongated structures are disentangled into their corresponding orientation planes and enhanced via multi-orientation vessel filtering. In addition, scale-selective OSs (in the domain of positions, orientations and scales R 2 ⋊ S 1 × R + ) are obtained by adding a scale adaptation to the wavelet transform. Features are optimally extracted by taking maximum orientation responses at multiple scales, to represent vessels of changing calibers. Finally, we train a Random Forest classifier for vessel segmentation. Extensive validations show that our method achieves a competitive segmentation, and better vessel preservation with less false detections compared with the state-of-the-art methods.